Study of Potential Utilization of Recycling Ablution Used Water, Case Study at Ulul Albaab Mosque, Universitas Pasundan, Bandung, Indonesia - Evi Afiatun; Sri Wahyuni; Jeanyta Harto (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2022)
The role of water in daily life, including activities in the mosque is very significant. The existence of the Ulul Albaab Mosque which is always busy with various congregation activities and activities carried out by students and the campus community affects the need for clean water. So far, the ablution used water at the Ulul Albaab Mosque has been dumped into the sewers. Measuring the quantity of water to determine the volume of ablution used water at the time of obligatory prayer is the first step to assessing its potential utilization. The number of congregation who perform ablution is directly proportional to the number of congregation of the Ulul Albaab Mosque. The average congregation of the mosque is 857 people/day and the average number who perform ablution is 778 people/day. The results showed that the volume of water used for ablution was 3.9 liters/person with an average time required for ablution of around 64 seconds. The use of recycling ablution water can be used for non-consumption needs.